Pengaruh Disiplin Kerja Dan Kompetensi Pegawai Terhadap Kepuasan Masyarakat Pada Pelayanan UPPMPTSP Kelurahan Kebon Jeruk Jakarta - Marsanda, Azahra; Sucipto, Rakhmat Hadi; Indah Annisa, Tri Hadi (CV Warnak Johanna Nusantara, 2025)
In public service, community satisfaction is a response to the quality of an organization's performance. This quantitative study aims to examine and prove the partial and simultaneous effects of work discipline and employee competence on community satisfaction. Work discipline and employee competence are two key factors that can enhance the quality of services provided by the Investment Management and One-Stop Integrated Service Unit in Kebon Jeruk Subdistrict, West Jakarta. The study used 100 samples of service users from this unit, selected through convenience sampling. Data were collected via questionnaires measured on a Likert scale. Data analysis employed descriptive and inferential techniques using SPSS Version 25. The results indicate that: 1) work discipline has a significant partial effect on community satisfaction; 2) employee competence has a significant partial effect on community satisfaction; 3) work discipline and employee competence simultaneously affect community satisfaction. The T-test results show work discipline with t-count 6.181 > t-table 1.984 and p-value 0.000, employee competence with t-count 3.559 > t-table 1.984 and significance 0.000, and the F-test with F-count 49.485 > F-table 3.090 and significance 0.000.